PEMBANGUNAN DEMOKRASI DAN PEMBANGUNAN EKONOMI – HUBUNGAN DAN PENGARUHNYA* - Larry Diamond; Ainur Rofieq (Governance, 2010)
Over the years the relationship between democracy and development has been comprehensively contested, and recent cross-national statistics as well as comparativehistorical data show that the relationship is not causal as conventionally perceived. Successful development has, for example, been achieved in both democracies andauthoritarian regimes, and similarly democracy has been sustained in countries with lower GNP than the traditional minimum threshold of 300 USD per capita per year. The relationship is also complicated by conceptual challenges in different regions of the world: different cultures delineate democracy and development differently and there no exact definitions of the two concepts.